2013
DOI: 10.1088/1748-9326/8/1/014029
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the impact of fungal spore ice nuclei on clouds and precipitation

Abstract: Some fungal spore species have been found in laboratory studies to be very efficient ice nuclei. However, their potential impact on clouds and precipitation is not well known and needs to be investigated. Fungal spores as a new aerosol species were introduced into the global climate model (GCM) ECHAM5-HAM. The inclusion of fungal spores acting as ice nuclei in a GCM leads to only minor changes in cloud formation and precipitation on a global level; however, changes in the liquid water path and ice water path a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
17

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(77 citation statements)
references
References 60 publications
4
56
0
17
Order By: Relevance
“…In autumn the relative amount of biomass in PM was estimated to be around ∼ 10 % (Supplement). Modelling studies have suggested that microorganisms may play an important role in the hydrological cycle in the boreal region (Sesartic et al, 2012(Sesartic et al, , 2013. However, the magnitude of upward lifting of microorganisms remains to be solved, and thus our results are preliminary in nature and need to be confirmed.…”
Section: Discussionmentioning
confidence: 72%
“…In autumn the relative amount of biomass in PM was estimated to be around ∼ 10 % (Supplement). Modelling studies have suggested that microorganisms may play an important role in the hydrological cycle in the boreal region (Sesartic et al, 2012(Sesartic et al, , 2013. However, the magnitude of upward lifting of microorganisms remains to be solved, and thus our results are preliminary in nature and need to be confirmed.…”
Section: Discussionmentioning
confidence: 72%
“…One of the first improvements that would benefit the PLAnET model would be validation on microbial fluxes that are not based solely on cultivated microorganisms. The ratio of culturable microorganisms to total microorganisms may range from 0.01 to 75 % and is generally below 10 % (see Burrows et al, 2009b, and references therein), meaning that PLAnET output needs scaling to be compared with the work, for example, of Burrows et al (2009a), Sesartic et al (2012) and Sesartic et al (2013). A simple comparison can be made between PLAnET simulated fluxes and fluxes reported in Burrows et al (2009a) using the scaling factor for the ratio of culturable to total bacteria for grasslands (302, Burrows et al, 2009b).…”
Section: Discussionmentioning
confidence: 99%
“…The larger-scale model would then be able to simulate the dispersion of the PBAs across the simulation domain, giving new insight in the potential of PBAs to impact precipitation, as well as exploring different scenarios about the potential pathways of transport of plant pathogens from the phyllosphere. In fact, given that some of the aforementioned models are able to simulate both gas-phase and aerosol chemistry, it would be possible to follow up the pioneering work of Burrows et al (2009a) and Sesartic et al (2013) on different spatiotemporal scales and investigate the changes in the outputs due to the insertion of a realistic PBA emission module.…”
Section: Discussionmentioning
confidence: 99%
“…Observed correlations between PBAP and IN concentrations during rain events over the continental United States further suggest an important role for PBAPs in the hydrological cycle Prenni et al, 2013). In contrast, recent modelling studies have found that PBAPs make little contribution to global ice nucleation (Hoose et al, 2010a, b;Sesartic et al, 2013). For example, Hoose et al (2010b) simulated that PBAPs contribute less than 0.6 % to the global average ice nucleation rate.…”
Section: Introductionmentioning
confidence: 96%